Pengaruh Islamic Governance Score, Leverage, Ukuran Perusahaan, dan Ukuran Dewan Komisaris Terhadap Kesehatan Finansial Bank Umum Syariah (Studi Empiris di BEI Periode 2013 Sampai 2016) - Yuniar Laeli Nur Faizah; Sri Hartiyah (Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an (UNSIQ) Wonosobo, 2018)
This study aims to analyze the effect of capital adequacy ratio, return on assets, non performing financing, operating expenses to operating revenues, financing to deposit ratio, third party fund, nisbah, and number of office to the market share of Islamic banking in Indonesia. Population in this study are quarterly financial statements of Sharia Commercial Banks and Sharia Business Units in Indonesia registered in BEI for the period December 2013 to 2016. The sampling technique in this study was conducted by purposive sampling method, so that 12 banks were obtained as research samples. The analytical method used in this study is multiple linear regression with the help of SPSS statistics. The influence of BUS does not affect the financial health of BUS, leverage does not negatively affect the financial health of BUS, the size of the company does not have a positive effect on the financial health of BUS, the size of the board of directors has no effect on the financial health of BUS. Keywords : Financial health of Islamic commercial banks, Islamic governance score, leverage, company size, and the size of the board of commissioners